The large, viscous thrombus is aspirated by using the cyclic suction technique - Lin Shenqi; Yu Ling; Hong Ruiting; Dong Runcheng; Liu Bohao; Ruan Wencong; Sun Tao; Zhou Dongqing; Zhou Yixuan; Chen Shi (BIO Web of Conferences)
With the development of socio-economic conditions and changes in people’s lifestyles, particularly the acceleration of population aging and urbanization, unhealthy living habits among residents have become increasingly prominent. Cardiovascular disease (CVD) risk factors have a growing impact on public health, and the incidence of CVD continues to rise. Current research focuses mainly on improving the safety and effectiveness of thrombectomy devices and reducing complications during surgical procedures. Additionally, researchers are exploring the application of these devices in specific patient groups, such as those with comorbid conditions. This project introduces an intelligent device based on an MCU (Microcontroller Unit). Starting with the overall hardware system design, it includes the development of the device casing, selection of the MCU, and design of the internal pipeline length according to the pressure tolerance of the human inferior vena cava during thrombectomy. A pressure control valve and a pressure gauge are installed to ensure that the suction pressure remains within a safe range tolerable for the human body throughout the procedure. Pressure sensor data is then used to develop algorithms and control programs, enabling precise control of the opening and closing actions of the positive and negative pressure solenoid valves at specified intervals. By using optimal timing data, the suction tube of the device can generate impacts to break large thrombi while effectively preventing them from escaping to other parts of the vessel during the suction process, ensuring the smooth completion of thrombectomy. Through its unique design and precise operation, this device can more effectively remove thrombi from blood vessels, overcoming the limitations and risks of traditional treatment methods. This technological innovation not only advances the overall technical capabilities of the medical industry but also provides physicians with a more efficient and convenient treatment tool, further improving the quality and efficiency of medical services. Moreover, by rapidly and effectively removing thrombi, this treatment reduces patient hospitalization time and medication use, thereby lowering medical costs. As the technology becomes more widespread and its application more common, the cost of this treatment method is expected to decrease further, providing more patients with an affordable and effective treatment option.